PERLINDUNGAN TERHADAP PEMENUHAN NAFKAH ANAK DALAM PELAKSANAAN PUTUSAN PERCERAIAN DI PENGADILAN AGAMA - Rohmad Agus Solihin (Indonesian Journal of Law and Islamic Law (IJLIL), 2020)
Parents are the first party responsible for protecting and fulfilling children's rights. The rights of children to parents begin when their children are born and breathe the air in this world. So since then the responsibility of parents to their children has also arisen. Among the rights of children that must be fulfilled by parents is the right to support. Regarding family income, fathers are obliged to provide for their children if they need them, so children are obliged to provide for their mother and father if they need them. If the father is in poverty or his income is insufficient, the obligation to provide for his children remains, does not die, and if the mother of the children is well off, he can be ordered to provide for his children, which is their father's obligation, but can be billed for return it. However, the income that the father (husband) cannot afford can be billed to be returned, the laws which in Indonesia have not regulated that far. Key Words: , ,